Factor Inputs and the Growth of the Manufacturing Sector among the East African Community Member States: Testing the Efficacy of the Extended Neoclassical Growth Hypothesis - Musiita, Benjamin; Jeke, Leward (Journal of Economics and Behavioral Studies, 2023)
The study aims to examine the relationship between input factors and growth rates in the output of the manufacturing sector in the five East African Community (EAC) member states. The relatively small manufacturing sector's GDP contribution to the combined GDP of the EAC member nations is the driving force behind this inquiry. We evaluate the applicability of the 1992 Mankiw, Romer, and Weil neoclassical growth framework and its subsequent developments in this study. Using a linear dynamic panel model, we utilize this methodology to obtain estimations using the first difference generalized method of moments (D-GMM. The study's findings make it clear that the gross capital formation input component is essential for forecasting changes in the rate of expansion of the manufacturing sector's output. Conversely, the East African Community's member states' manufacturing sector output growth does not seem to be much impacted by variables such as adjusted population growth and human capital. Based on our research, the East African Community (EAC) member states' output fluctuations in the manufacturing sector may be partially explained by the neoclassical growth model and its expansions. This shows that the growth framework that has been chosen might not be thorough enough to provide a thorough assessment of the variables influencing the expansion of the manufacturing sector output in the EAC member nations. The findings of our study indicate that the manufacturing sector’s output growth in the EAC member states could be enhanced through the implementation of policies and programs that provide incentives for augmenting capital stocks. This can be accomplished by increasing investments from the domestic private sector as well as foreign direct investments.
Keywords: Manufacturing sector output; Extended neoclassical growth theory; D-GMM; EAC member states